2015
DOI: 10.1186/s40510-015-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between tooth size and interarch relationships in children with operated complete unilateral cleft lip and palate

Abstract: BackgroundTo evaluate mesiodistal tooth width of patients with UCLP comparing tooth size in different Goslon Yardstick scores and between cleft and noncleft sides.MethodsThe Department of Orthodontics at Bauru Dental School and Hospital of Rehabilitation of Craniofacial Anomalies – University of Sao Paulo. Hundred forty-four pairs of dental casts of patients with UCLP. These dental casts were divided into 3 groups: group I (patients with Goslon rating of 1 and 2), group II (Goslon rating of 3) and group III (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…A previous study demonstrated that narrow canines were preferred in the position of lateral incisors. 33 No mesiodistal tooth size asymmetries were found for the maxillary central incisors in this study, corroborating the study by Santos et al 34 However, other previous studies have reported smaller anterior tooth size on the cleft side in UCLP, compared to noncleft side. [35][36][37] Tooth size and shape differences of the cleft side central incisors may be associated with the dental anomalies pattern.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study demonstrated that narrow canines were preferred in the position of lateral incisors. 33 No mesiodistal tooth size asymmetries were found for the maxillary central incisors in this study, corroborating the study by Santos et al 34 However, other previous studies have reported smaller anterior tooth size on the cleft side in UCLP, compared to noncleft side. [35][36][37] Tooth size and shape differences of the cleft side central incisors may be associated with the dental anomalies pattern.…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of congenitally missing teeth in the general population has been reported within a range of 0.027 to 10.1 %, which varies greatly according to geographic location and race [57]. Clefts of all types are often associated with congenitally missing teeth,[8] and when compared with the general population, subjects with CLP have always been found to have a higher prevalence of dental anomalies, such as variations in tooth number and position, and reduced tooth dimensions, most of which are localized in the area of the cleft defect [911]. Rullo et al examined the prevalence of different types of dental anomalies in children with cleft and found that congenital absence of the cleft-side lateral incisor was observed in 40 % of the samples and a total of 30 % patients showed supernumerary teeth at the incisors region [12].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of congenitally missing teeth in the general population has been reported within a range of 0.027 to 10.1%, which varies greatly according to geographic location and race 8 . When compared with the general population, subjects with CLP have always been found to have a higher prevalence of dental anomalies, such as variations in tooth number and position, and reduced tooth dimensions, most of which are localized in the area of the cleft defect 9 . The frequency of patients with congenitally missing teeth is 1.6 to 9.6%, as reported by Graber 10 .…”
Section: Introductionmentioning
confidence: 99%